2022
DOI: 10.1016/j.envc.2021.100428
|View full text |Cite
|
Sign up to set email alerts
|

Time to recovery from Covid-19 and its associated factors among patients hospitalized to the treatment center in South Central Ethiopia

Abstract: Coronavirus outbreak was a public health emergency. The surge of new confirmed cases and deaths was observed in developing countries due to the occurrence of new variants. However, factors associated with the duration of recovery among admitted patients remained uncertain. Therefore, we assessed factors associated with time to recovery from Covid-19 among hospitalized patients at the treatment center in South Central, Ethiopia. We employed a retrospective cross-sectional study among 422 patients hospitalized a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 31 publications
1
10
1
Order By: Relevance
“…The majority of COVID-19 patients have mild to moderate symptoms, whereas 14% of patients have severe symptoms and 5% are in serious condition ( 11 ). The median time to recover from COVID-19 is 13 days, with an interquartile range of 9–17 days ( 12 ). Despite already having negative PCR test result, 1 in 5 people may have symptoms for 5 weeks or more, while 1 in 10 may be symptomatic for 12 weeks or more ( 13 ).…”
Section: Discussionmentioning
confidence: 99%
“…The majority of COVID-19 patients have mild to moderate symptoms, whereas 14% of patients have severe symptoms and 5% are in serious condition ( 11 ). The median time to recover from COVID-19 is 13 days, with an interquartile range of 9–17 days ( 12 ). Despite already having negative PCR test result, 1 in 5 people may have symptoms for 5 weeks or more, while 1 in 10 may be symptomatic for 12 weeks or more ( 13 ).…”
Section: Discussionmentioning
confidence: 99%
“…Our study findings reported the minimum duration to recovery time from COVID-19 patients was 10.95 days in male patients with a mean age of 36.1±19.0 and 11.75 days in female patients with a mean age of 34.7±20.6. Recent findings from various other studies report 13 days in Ethiopia, 17 days in Hefei, China, 17 days in Vietnam, and 10 days in India [ 18 - 21 ]. However, the mean recovery time in both male and female patients was relatively lower than other reports of an average recovery time of COVID-19 patients from 18 days to 22 days and higher than reports of an average recovery time of 6.5 days [ 22 - 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…When considered individually, the clinical importance of upper abdominal symptoms is low, but it is more obvious when considered collectively. Various studies have suggested that psychosocial factors may be responsible for the symptoms of non-ulcer dyspepsia; however, it is still debatable whether symptoms can be used to accurately predict a diagnosis of functional dyspepsia instead of chronic peptic ulceration or other organic diseases [3,4].…”
Section: Introductionmentioning
confidence: 99%